Механічне демпфування у системі енергоформуючого керування синхронною машиною з постійними магнітами - Білецький, Юрій; Щур, Ігор; Щербовських, Сергій (Видавництво Львівської політехніки, 2013)
For the control of permanent magnet synchronous motor in electromechanical system an energyshaping control systems have been used. The regulation in such systems is realized by injection of additional damping of current vector projections on dq-axes and some correction coefficient. The energy-shaping control systems with present regulation elements provide worse response compare with classical systems and are hard to be configured. The main aim of this article is to suggest an alternative structure of energyshaping control system without these disadvantages. For this purpose the energy-shaping control system structures with mechanical damping as regulation element are proposed. There are presented the advantages of mechanical damping injection as well. To exam the proposed system work the comparative researches of its work with old structure system work were carried out. So, it might be said that for effective regulation in electromechanical system with permanent magnet synchronous motor the energy-shaping control system can be injected with mechanical damping. Such system provides high response and is simple to configure.
Keywords: синхронна машина з постійними магнітами; енергетичний підхід; векторне керування; система енергоформуючого керування; додаткове демпфування